Atlanticalymene, a new genus of Middle Ordovician (Darriwilian) calymenine trilobites, and revision of the calymenoidean genus Protocalymene Ross - Adrain, Jonathan M.; Karim, Talia S.; Mcadams, Neo E.b. (Zootaxa, 2020)
Middle Ordovician (Darriwilian) species representing early Laurentian occurrences of the Subfamily Calymeninae Milne Edwards, 1840 (=Flexicalymeninae Siveter, 1977) are assigned to Atlanticalymene n. gen. (type species: A. bardensis n. sp. from the Table Cove Formation, western Newfoundland, Canada). They have routinely been confused with the older (Dapingian) calymenoidean taxon Protocalymene Ross, 1967. Revision of the type species of Protocalymene, P. mcallisteri Ross, 1967, from the Antelope Valley Formation, Funeral Mountains, California, indicates that it is not a calymenine, and that while it is clearly a calymenoidean its close affinity is otherwise difficult to determine. A single genuine calymenine species is known from the Laurentian Dapingian, and revised here as “Calymeninae n. gen.? n. sp. A” from the Antelope Valley Formation, Nevada, USA. A species from the Dapingian of Tarim, known from a single partial cranidium, appears to represent an older, extra-Laurentian species of Atlanticalymene.